ANALISA EFFISIENSI PLTU PAITON KETIKA HIGH PRESSURE HEATER (HPH 7) INSERVICE DAN OUTSERVICE - Sigit Untoro; Nova Risdiyanto Ismail; Akhmad Farid; Purbo Suwandono (Jurnal Energi dan Teknologi Manufaktur, 2022)
National electricity needs are always increasing, for that the efficiency of power plants needs to be maintained and expected to be improved. To maintain the efficiency of the power plant, it is necessary to feed water system as a provider of feed water before entering the boiler in good condition and one of the equipment is the High Pressure Heater (HPH). In Paiton Power Plant there are HPH numbers 5.6 and 7. This research aims to compare the efficiency of power plants and the losses caused when pltu operates in hph 7 inservice and outservice conditions. The research method used is a simulation in the simulator room of PLTU PT. PJB UP Paiton 1 & 2. From the data obtained then done calculations. Research produces the efficiency value of PLTU when in HPH 7 inservice condition is 33.40% and when outservice is 29.20%. The need for coal to increase the temperature lost due to HPH 7 outservice amounted to 11.11 Tons / hour, so that the losses caused by the increase in coal flow amounted to Rp 1,204.896.000 per year.